2018
DOI: 10.1186/s13068-018-1093-0
|View full text |Cite
|
Sign up to set email alerts
|

Novel optimization strategy for tannase production through a modified solid-state fermentation system

Abstract: BackgroundHigh amounts of insoluble substrates exist in the traditional solid-state fermentation (SSF) system. The presence of these substrates complicates the determination of microbial biomass. Thus, enzyme activity is used as the sole index for the optimization of the traditional SSF system, and the relationship between microbial growth and enzyme synthesis is always ignored. This study was conducted to address this deficiency. All soluble nutrients from tea stalk were extracted using water. The aqueous ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…SSF can be used in case of nearly or completely absence or near absent of free liquid when using a solid substrate as raw materials. The advantages of this method are the use low cost raw materials, little energy consumption and small bioreactor dimensions because of the concentrated media (Couto &Toca-Herrera, 2007 andWu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…SSF can be used in case of nearly or completely absence or near absent of free liquid when using a solid substrate as raw materials. The advantages of this method are the use low cost raw materials, little energy consumption and small bioreactor dimensions because of the concentrated media (Couto &Toca-Herrera, 2007 andWu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…At present, the production of secreted tannase for industrial applications involves the utility of either crude or semi-purified enzyme prepared from submerged or solid-state cultures of Aspergillus niger or Aspergillus oryzae fermented in the presence of tannic acid (Aguilar et al 2007 ; Varadharajan et al 2017 ; Wu et al 2018 ). However, low yield and purity, batch variability and a poor understanding of catalytic mechanism of tannase have limited its utility.…”
Section: Introductionmentioning
confidence: 99%
“…Kumar et al (2007) reported the decrease in tannase production by use of complex nitrogen source, yeast extract. Yeast extract as organic nitrogen source is rarely chosen in traditional SSF due to its very slight effect on the synthesis of enzyme as reported by Wu et al (2018).…”
Section: Discussionmentioning
confidence: 99%
“…Selvaraj and Vytla (2018) determined 1% tannic acid as medium component using CCD for optimal tannase synthesis by B. gottheilii M2S2. RSM optimized components of 7.49% tannin, 8.11% glucose, 2.25% yeast extract and 9.26% (NH 4 ) 2 SO 4 were obtained by Wu et al (2018) for highest tannase productivity from Aspergillus tubingensis CICC 2651 using tea stalk under SSF. So, the requirement of medium composition and their concentrations could vary depending on microorganism or substrate used.…”
Section: Discussionmentioning
confidence: 99%